Polymer Nanoparticles Prepared by Supercritical Carbon Dioxide for in Vivo Anti-cancer Drug Delivery - Hua, Maofang; Hua, Xiufu (Nano-Micro Letters, 2013)
A new approach for producing polymer nanoparticles made of bovine serum albumin-poly(methyl methacrylate) conjugate by precipitating in supercritical CO2 is reported. The nanoparticles were loaded with the anti-tumor drug camptothecin. With albumin serving as a nutrient to cells, the drug-encapsulated nanoparticle shows an enhanced ability to kill cancer cells compared to that of the free drug in solution both in vitro and in vivo.